2011
DOI: 10.1103/physrevb.83.125306
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between electrical transport properties of GeMn thin films and Ge substrates

Abstract: We present evidence that electrical transport studies of epitaxial p-type GeMn thin films fabricated on highresistivity Ge substrates are severely influenced by parallel conduction through the substrate, related to the large intrinsic conductivity of Ge due to its small band gap. Anomalous Hall measurements and large magnetoresistance effects are completely understood by taking a dominating substrate contribution as well as the measurement geometry into account. It is shown that substrate conduction persists a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…11 and 12. Less exotic mechanism was suggested by Zhou et al 13 that pointed out that much of the phenomena, in particular nonmonotonous Hall angle, can be explained by parallel conduction of two charge carriers generated by, e.g., two-level Mn acceptors in Ge. Supporting evidence for the two-carrier transport, although in a different geometrical implementation, was demonstrated by Sircar et al 14 that showed that parallel conduction along a doped layer and Ge substrate can generate very large magnetoresistance and non-monotonic Hall effect remarkably similar to the previous GeMn data, also when non-magnetic GeB films were grown on top of Ge substrates. It was thus concluded that spectacular properties of GeMn systems are not a consequence of alloying of magnetic Mn with Ge but result from parallel conduction along thin conducting doped epilayer and thick resistive Ge substrate.…”
Section: Introductionsupporting
confidence: 52%
“…11 and 12. Less exotic mechanism was suggested by Zhou et al 13 that pointed out that much of the phenomena, in particular nonmonotonous Hall angle, can be explained by parallel conduction of two charge carriers generated by, e.g., two-level Mn acceptors in Ge. Supporting evidence for the two-carrier transport, although in a different geometrical implementation, was demonstrated by Sircar et al 14 that showed that parallel conduction along a doped layer and Ge substrate can generate very large magnetoresistance and non-monotonic Hall effect remarkably similar to the previous GeMn data, also when non-magnetic GeB films were grown on top of Ge substrates. It was thus concluded that spectacular properties of GeMn systems are not a consequence of alloying of magnetic Mn with Ge but result from parallel conduction along thin conducting doped epilayer and thick resistive Ge substrate.…”
Section: Introductionsupporting
confidence: 52%
“…As shown in figure 5, the slope of the linear B variation decreased upon removing the Pt capping layer. The influence of the Pt layer on the measurement can be evaluated using the following formula derived from a twolayer conduction model [38]:…”
Section: Analysis and Discussionmentioning
confidence: 99%
“…Nevertheless, many researchers have reported on the superior properties of Ge substrates. Sircar et al described the electron transport properties of Ge substrates with epitaxial p-type GeMn thin films, which gives rise to an effective 2-layer conduction scheme [2].…”
Section: Introductionmentioning
confidence: 99%